Synthesis, Characterization, and Antibacterial Activity Test of Geothermal Silica/AgNO3 Thin Film - Astuti, Yayuk; Rahayu, R.A. Yunita Suci; Arnelli, Arnelli (Molekul, 2023)
Geothermal silica waste offers convenient, economical, and environmentally friendly material with high hydrophobicity to produce thin films. Silica-thin films from geothermal waste using the sol-gel method, though, no addition of AgNO3 was conducted for antibacterial functions. This study aims to produce silica-thin films from geothermal waste with the addition of AgNO3 and analyze the antibacterial activity. The procedures carried out in this research were (i) an acid leaching process using HNO3; (ii) the production of silica thin film with and without the addition of AgNO3; (iii) thin film characterization including a water contact angle measurement (WCA), XRF, FTIR, XRD and SEM-EDX on silica thin film samples with and without the addition of AgNO3; and (iv) antibacterial activity test. The results show the optimum HNO3 concentration for the acid leaching process was 20%, yielding 99.08% SiO2 by mass. The WCA of the silica thin film in the presence and absence of AgNO3 reached a value of ±160°, indicating the addition of AgNO3 did not decrease the contact angle of the silica thin film. This research employed smart deconvolution of IR Spectra using Fityk software which reveals a higher area ratio for Si-O-Si relative to Si-OH. Furthermore, it was observed that the silica thin films exhibited an amorphous morphology, both without and with the addition of AgNO3, with Ag discovered to be dispersed on the thin film. However, despite the presence of Ag, both TF20 and TF20+Ag samples were found to be ineffective in inhibiting bacterial growth, as evidenced by bacteria-free zones on the samples.